Switch semi-active control of the floating raft vibration isolation system - Weng, Zeyu (Strojniški vestnik, 2022)
Switch semi-active control is introduced to improve the performance of the floating raft vibration isolation system on isolating vibration in the vicinity of the resonance frequency. A switch-controllable linear damper based on the electromagnetic damping principle is developed, whose characteristic parameters are obtained by experiment. The dynamic model of a semi-active control floating raft vibration isolation system is established, and two switch control algorithms are proposed. Algorithm 1 aims to minimize the kinetic energy of the raft, and Algorithm 2 balances minimizing the kinetic energy of the raft and minimizing the input energy of the system. The simulations of the original system, the system with the controllable damper, and the system with the damper controlled by the algorithms are carried out. The vibration acceleration responses of the foundation of the systems are used to evaluate the vibration isolation effect. The results show that the switching semi-active control using Algorithms 1 and 2 can significantly suppress the vibration of the system near the resonance frequency. Finally, the test platform of the switch’s semi-active controlled floating raft vibration isolation system is built, and the simulation results are verified by the experimental result.
Keywords: floating rafts; polaktivna regulacija; semi-active control; splavi; switch algorithm; vibration isolation; vibroizolacija; vklopni algoritem